First results on the running coupling in QCD with two massless flavours - Bode, Achim; Frezzotti, Roberto; Gehrmann, Bernd; Hasenbusch, Martin; Heitger, Jochen; Jansen, Karl; Kurth, Stefan; Rolf, Juri; Simma, Hubert; Sint, Stefan; Sommer, Rainer; Weisz, Peter; et al. (Physics letters, 2001)
We report on the non-perturbative computation of the running coupling of two-flavour QCD in the Schrödinger functional scheme. The corresponding Λ-parameter, which describes the coupling strength at high energy, is related to a low energy scale which still remains to be connected to a hadronic “experimentally” observable quantity. We find the non-perturbative evolution of the coupling important to eliminate a significant contribution to the total error in the estimated Λ-parameter.
Gesehen am 05.07.2022